The Influence of Customer Relationship Marketing Strategy on Student Satisfaction at SMP IT Rahmaniyah in Cibinong – Bogor Regency - Agus Purwo Wicaksono; Abdul Rosyid (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
Through customer relationships, companies can provide added value to customers, create customer satisfaction by understanding their wants and needs, and make efforts to get to know customers better. By providing maximum service to customers, in this case the parties who directly relate and interact with customers will create a close relationship between the company and customers. The purpose of this study was to determine the influence of the Customer Relationship Marketing Strategy on the satisfaction of the parents of SMP IT Rahmaniyah. The customer relationship marketing strategy is one of the company's efforts to deal with changes that occur in the business environment. Increasingly fierce competition, technological advances and changes in market needs and wants. In essence, relationship marketing reflects a paradigm shift in marketing, which was originally focused on customer transactions/acquisition to become customer relations/retention. The hypothesis in this study is that it is suspected that there is a positive and significant influence from the Customer Relationship Marketing Strategy on Satisfaction. This research was conducted at SMP IT Rahmaniyah which is located at Jalan. Kostrad Division No.25 Cibinong, Bogor Regency, West Java. The population is 430 people, with a random sampling technique of 20%, a total of 86 people. Data analysis techniques in the form of descriptive analysis, simple linear regression analysis, correlation coefficient, coefficient of determination, and t test. Based on the results of data analysis and discussion, it can be concluded that the influence of the Customer Relationship Marketing Strategy on the Satisfaction of Guardians of SMP IT Rahmaniyah with a correlation value of (R) 0.696 or 69% and the influence between the two variables the coefficient of determination is (Rsquare) of 0.484 or 48 %. With a tcount value of 8.875, it is significant at 0.000 and a confidence level of 0.05.